The credit scoring model as an alternative of credit evaluation in Agrobanco - Calderón Romero, Lizardo (2018)
In recent years, Peru has experienced strong growth in the financial sector, mainly focused on the credit sector, which has allowed the economy to be boosted, which is not the case for credits oriented to the agricultural sector due to its level of risk, reason whereby the Peruvian government creates Agrobanco as an entity focused on the agricultural sector through the placement of agricultural loans. The objective of the research is to develop a Credit Scoring model that allows to support the immediate evaluation of the agricultural credit, due to the deficient and slow of it by Agrobanco. Likewise, the methodology used is based on a Credit Scoring model of predictive nature, which proposes a method of marginal effects and the evaluation of the entire portfolio of the entity from the period 2009 to 2015. The results obtained in the investigation determine that the independent variables: rate, period, guarantee, age, single, normal and seniority, are statistically significant in the delinquency of the loans granted, however the variables, amount, woman and hectare are not representative. The conclusions of the investigation are that it is fulfilled as socio-economic determinants, statistically, the variables: rate, period, guarantee, age, single, normal grades and seniority.